Human capital formation and public debt: growth and welfare effects of three different deficit policies. Issue 4 (1st October 2016) - Greiner, Alfred
Abstract : We analyze an endogenous growth model public educational spending. We show that the balanced budget policy and the policy with a slight deficit yield higher growth than a debt policy where public debt grows at the same rate as GDP, unless the government is a creditor. As concerns welfare, it can be demonstrated that a strong deficit policy yields lower welfare than a balanced budget and a slight deficit policy, unless initial debt ratios are low and the intertemporal elasticity of substitution is high. Finally, there may exist an inverted U-shaped relation between welfare and deficit-financed educational spending.